Method for improving performance of concrete member by using freezing enhancement unit and prepared concrete member
By building a refrigeration reinforcement unit in the concrete component and combining it with concrete hydration, the problem of insufficient bonding force between fiber reinforced concrete and ordinary concrete is solved, and the mechanical properties and toughness of concrete components are significantly improved.
Patent Information
- Application Number
- CN202510229383.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-28
AI Technical Summary
The interface bonding force between existing fiber-reinforced concrete and ordinary concrete is insufficient, resulting in the separation of the fiber-reinforced layer and concrete, unable to exert the expected reinforcement effect, and the construction is complex, affecting the mechanical properties of concrete components.
The refrigeration reinforcement unit is prepared by rapid refrigeration technology, which is built into the stress concentration area of concrete, and the fiber reinforcement unit is combined with the hydration of concrete through the refrigeration method to form a strong and integrated composite material.
It significantly improves the crack resistance, tensile strength, flexural strength and shear strength of concrete components, improves interface adhesion, reduces plastic damage, and avoids the problems of material layering or interface gaps.
Smart Images

Figure CN119897938A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering, and in particular relates to a method for improving the performance of a concrete component by utilizing a freezing enhancement unit and the prepared concrete component. Background Art
[0002] Ordinary concrete itself has the characteristics of low tensile strength, poor shear resistance and insufficient toughness. It is easy to crack under the combined action of external environment and load, and has the brittle problem that cracks are difficult to control after cracking. Fiber reinforced concrete is a ductile concrete material, and its ultimate strain is dozens of times higher than that of ordinary concrete. The combination of fiber reinforced concrete and ordinary concrete is one of the effective ways to improve the cracking of concrete components.
[0003] Fiber reinforced concrete is mainly used to improve the mechanical properties of structures. Parts and key structural elements made of fiber reinforced concrete and fiber reinforced concrete reinforcement layers can improve the mechanical properties of concrete. Fiber reinforced structural components show good failure modes and structural responses. The brittle failure mode of traditional concrete can be prevented by modifying a few crack modes to multiple crack modes. The fiber bridging effect can effectively resist the formation and expansion of cracks, thereby improving ductility, energy absorption and damage tolerance.
[0004] The existing fiber concrete and ordinary concrete combination adopts the commonly used combined reinforcement method of in-situ pouring, prefabrication or spraying of fiber concrete reinforcement layer. The bonding characteristics between the fiber concrete reinforcement layer and the ordinary concrete interface are the key factors that mainly control the reinforcement efficiency. However, the current reinforcement process adopts layered pouring, which has problems such as complex interface treatment methods, the bonding performance is easily affected by construction, and the bonding strength needs to be further improved. The reinforcement method of adding fiber-reinforced composite materials to concrete requires the subsequent removal of part of the concrete for groove reinforcement, which causes damage to the concrete as a whole and makes the failure mode more complicated. Therefore, it is of great significance to develop a technology that improves the mechanical properties of concrete, has good interface bonding with concrete, and reduces the complexity of construction to improve the performance of concrete components. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for improving the performance of concrete components by using frozen reinforcement units and the prepared concrete components, so that the crack resistance of the concrete components is improved, the plastic damage of concrete is reduced, and the toughness of concrete is improved. At the same time, the fiber reinforcement units have good interface properties with ordinary concrete, further improving the mechanical properties of concrete.
[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is: The object of the present invention is to provide a method for improving the performance of a concrete component, comprising the following steps: (1) Using rapid freezing technology to prepare cryoenhancement units; (2) The stress concentration area of the concrete member is wrapped with at least one frozen reinforcement unit in a frozen state by pouring, and the thawed frozen reinforcement unit is combined with the concrete member through a hydration reaction by curing.
[0007] Further, the process of preparing the cryoenhancement unit is as follows: Before the initial setting of the reinforcement unit, the reinforcement unit is frozen and formed within 60 minutes, and its core temperature is reduced to -40~-10℃.
[0008] Furthermore, the enhancement unit is Engineering fiber reinforced cementitious composites (ECC).
[0009] Furthermore, the engineering fiber reinforced cement-based composite material is polyvinyl alcohol fiber reinforced concrete or steel fiber reinforced concrete.
[0010] Furthermore, the rapid freezing technology uses liquid nitrogen freezing, dry ice freezing or quick freezer freezing.
[0011] Furthermore, the freezing enhancement units are fitted to each other or have gaps therebetween.
[0012] Furthermore, the stress concentration area is a tension area or a shear area of the concrete member.
[0013] Furthermore, the spacing between the frozen reinforcement units in the shear zone should not be greater than 1 / 2 of the concrete height.
[0014] Furthermore, the specific process of curing in step (2) is: normal curing after pouring is completed, so that the frozen reinforcement unit naturally melts into slurry and combines with the hydration of the concrete component.
[0015] Furthermore, during pouring in step (2), the concrete properties of the frozen enhancement unit used are higher than the material properties of the concrete to be enhanced.
[0016] Another object of the present invention is to provide a concrete component, which is prepared by the above method.
[0017] Beneficial effects of the present invention: 1. In the traditional fiber-reinforced concrete component mechanical performance technology, when the fiber-reinforced unit replaces part of the concrete, the interface problem of insufficient interface bonding between the two is prone to occur, which makes it impossible to exert the performance of the fiber concrete, especially in the stress concentration area, which easily leads to the separation of the fiber-reinforced layer and the concrete, and the expected reinforcement effect cannot be exerted. The present invention prepares the fiber-reinforced unit in a frozen state by adopting the rapid freezing technology, so that the fiber-reinforced unit is combined with the concrete in the form of a frozen block during the concrete pouring process. When the frozen fiber-reinforced unit is melted into a slurry, it can better combine with the concrete to react with hydration to form a strong and tough composite material, which effectively solves the interface problem between the fiber concrete reinforcement layer and the concrete in the traditional technology. In this way, not only the interfacial bonding force is enhanced, but also the stability of the combination of the two is guaranteed, and the phenomenon of material stratification or interface gaps in the traditional scheme is avoided, which leads to a decrease in the mechanical properties of the concrete component.
[0018] 2. Traditional concrete components are often prone to crack expansion in stress concentration areas, resulting in a sharp decline in the mechanical properties of the components, especially the reduction in bending and shearing resistance. In order to improve these properties, it is usually necessary to add fiber reinforcement materials (such as steel fibers or polymer fibers) to concrete. Although these conventional fiber reinforcement materials can enhance the performance of concrete materials, for components, the improvement effect on the stress concentration area is not targeted, and the construction is complicated and the full-section admixture cost is high. The present invention significantly improves the performance of concrete components by embedding the frozen fiber reinforcement unit into the stress concentration area of concrete, and combining the fiber reinforcement unit with the concrete hydration reaction by resurrection after freezing. The high toughness and crack control ability of the added fiber reinforcement material can effectively inhibit the crack expansion of concrete under tensile stress, and enhance the crack resistance, tensile strength, bending strength and shear strength of concrete. Especially in the stress concentration area of concrete components, the embedding of fiber reinforcement materials can directly improve the strength and ductility of the area, thereby improving the overall crack resistance and mechanical properties of concrete components.
[0019] 3. Fiber-reinforced concrete technology usually adopts external wrapping or layered construction to embed fiber-reinforced materials into the outside or surface of concrete. When the fiber-reinforced material is wrapped on the outside of the concrete, due to the construction factors between the two or the change of ambient temperature, it is easy to cause a gap between the external wrapping material and the concrete, thereby affecting the stability of the entire structure. When the fiber-reinforced external wrapping or layered construction method is prone to microcracks, it is easy to be affected by external ultraviolet rays, atmosphere, temperature alternation and other environmental effects, as well as corrosion and aging effects such as rainwater corrosive media, which will cause fiber aging and failure, and ultimately affect the mechanical properties of concrete. Different from the external fiber-reinforced concrete technology, the present invention adopts the method of built-in fiber-reinforced units, directly embeds the fiber-reinforced units in the stress concentration area of concrete, and integrates the fiber-reinforced units with the concrete by freezing and resurrection. Since the fiber-reinforced unit is built into the concrete component, it avoids the direct influence of the external environment on the fiber-reinforced unit itself, thereby effectively preventing the crack expansion and concrete stratification caused by the external fiber reinforcement. In addition, the built-in method can ensure that the fiber reinforcement and concrete form an integral structure, which not only improves the overall mechanical properties of the concrete component, but also avoids the structural defects in the traditional external wrapping method. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The bending strength test result diagram of the concrete beam with built-in freezing enhancement unit prepared in Examples 1 to 3; Figure 2 The bending strength test results of concrete beams after treatment in Example 1 and Comparative Examples 1 to 4 are shown; Figure 3 This is a graph showing the shear bearing capacity test results of the concrete beams with built-in freezing enhancement units prepared in Examples 4 to 6; Figure 4 The shear bearing capacity test results of the concrete beams after being treated in Example 4 and Comparative Examples 5 to 8 are shown; Figure 5 This is a structural schematic diagram of a concrete beam with built-in frozen reinforcement units in the tension zone; Figure 6 This is a structural diagram of a concrete beam with built-in frozen reinforcement units in the shear zone; Figure 7 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0021] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected. Example
[0022] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 691kg / m cement 3 、Water 364kg / m 3 、Fly ash 565kg / m 3 , Quartz sand 452kg / m 3 , polycarboxylate water reducer 18kg / m 3 , the content of polyvinyl alcohol fiber (PVA) is 2%, and the water-binder ratio is 0.29; The prepared fiber reinforced concrete was poured into a mold and quickly frozen with liquid nitrogen before initial setting to form a frozen reinforced unit. The freezing temperature was set at -40°C. The center temperature of the fiber reinforced concrete unit reached -40°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. Arrange one freezing reinforcement unit at the center of the bottom of the tensile zone of the beam mold, 45mm from the concrete beam side, and the other two freezing reinforcement units are arranged at 60mm from the bottom of the beam, with a spacing of 110mm. After being arranged at the corresponding positions of the tensile zone, quickly pour the concrete slurry until it fills the beam mold, so that the concrete wraps the freezing reinforcement unit; After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components. Example
[0023] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 691kg / m cement 3 、Water 364kg / m 3 、Fly ash 565kg / m3 , Quartz sand 452kg / m 3 , polycarboxylate water reducer 18kg / m 3 , the content of polyvinyl alcohol fiber (PVA) is 2%, and the water-binder ratio is 0.29; The prepared fiber reinforced concrete was poured into a mold and quickly frozen with dry ice before initial setting to form a frozen reinforced unit. The freezing temperature was set at -20°C. The center temperature of the fiber reinforced concrete unit reached -20°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. Arrange one freezing reinforcement unit at the center of the bottom of the tensile zone of the beam mold, 45mm from the concrete beam side, and the other two freezing reinforcement units are arranged at 60mm from the bottom of the beam, with a spacing of 110mm. After being arranged at the corresponding positions of the tensile zone, quickly pour the concrete slurry until it fills the beam mold, so that the concrete wraps the freezing reinforcement unit; After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components. Example
[0024] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 801kg / m cement 3 、Water 143kg / m 3 、Fly ash 100kg / m 3 , Quartz sand 452kg / m 3 , silica fume 100kg / m 3 , polycarboxylate water reducer 35kg / m 3 , steel fiber content is 2%, water-binder ratio is 0.14; The prepared fiber reinforced concrete is poured into a mold and frozen in a quick freezer before initial setting to form a frozen reinforced unit. The freezing temperature is set at -10°C. The center temperature of the fiber reinforced concrete frozen reinforced unit reaches -10°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. Arrange one freezing reinforcement unit at the center of the bottom of the tensile zone of the beam mold, 45mm from the concrete beam side, and the other two freezing reinforcement units are arranged at 60mm from the bottom of the beam, with a spacing of 110mm. After being arranged at the corresponding positions of the tensile zone, quickly pour the concrete slurry until it fills the beam mold, so that the concrete wraps the freezing reinforcement unit; After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components. Example
[0025] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 691kg / m cement 3 、Water 364kg / m 3 、Fly ash 565kg / m 3 , Quartz sand 452kg / m 3 , polycarboxylate water reducer 18kg / m 3 , the content of polyvinyl alcohol fiber (PVA) is 2%, and the water-binder ratio is 0.29; The prepared fiber reinforced concrete slurry is poured into a mold, and liquid nitrogen is used to quickly freeze it before initial setting to form a frozen reinforced unit. The freezing temperature is set at -40°C, and the center temperature of the fiber reinforced concrete frozen reinforced unit reaches -40°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. 12 freezing reinforcement units are arranged symmetrically at an angle of 45° on both sides of the beam mold in the shearing zone. The spacing between the freezing reinforcement units in each shearing zone is 60 mm. After being arranged at the corresponding positions of the beam mold in the shearing zone, concrete slurry is quickly poured until the beam mold is filled, so that the concrete wraps the fiber-reinforced concrete freezing reinforcement units. After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components. Example
[0026] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 691kg / m cement 3 、Water 364kg / m 3 、Fly ash 565kg / m 3 , Quartz sand 452kg / m 3 , polycarboxylate water reducer 18kg / m 3 , the content of polyvinyl alcohol fiber (PVA) is 2%, and the water-binder ratio is 0.29; The prepared fiber reinforced concrete was poured into a mold and quickly frozen with dry ice before initial setting to form a frozen reinforced unit. The freezing temperature was set at -30°C. The center temperature of the fiber reinforced concrete unit reached -30°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. Arrange 12 frozen reinforcement units symmetrically at an angle of 45° on both sides of the beam in the shear zone, with a spacing of 60 mm between the frozen reinforcement units in each shear zone. After being arranged at the corresponding positions of the beam mold shear zone, quickly pour concrete slurry until the beam mold is filled, so that the concrete wraps the fiber-reinforced concrete frozen reinforcement units; After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components. Example
[0027] A method for improving the performance of concrete components by using frozen fiber reinforced units, the specific process is as follows: The raw material of fiber reinforced concrete contains 801kg / m cement 3 、Water 143kg / m 3 、Fly ash 100kg / m 3 , Quartz sand 452kg / m3 , silica fume 100kg / m 3 , polycarboxylate water reducer 35kg / m 3 , steel fiber content is 2%, water-binder ratio is 0.14; The prepared fiber reinforced concrete is poured into a mold and frozen in a quick freezer before initial setting to form a frozen reinforced unit. The freezing temperature is set at -10°C. The center temperature of the fiber reinforced concrete frozen reinforced unit reaches -10°C within 60 minutes to obtain a frozen reinforced unit. Two longitudinal steel bars with a diameter of 16 mm are placed at the bottom of the beam mold, and two longitudinal steel bars with a diameter of 8 mm are placed at the top of the beam mold. The steel bars are HRB400 grade, the stirrups are HRB335 grade steel bars with a diameter of 8 mm, and the spacing is 80 mm. The bent steel bars are HRB335 grade steel bars with a diameter of 8 mm. Arrange 12 frozen reinforcement units symmetrically at an angle of 45° on both sides of the beam in the shear zone, with a spacing of 60 mm between the frozen reinforcement units in each shear zone. After being arranged at the corresponding positions of the beam mold shear zone, quickly pour concrete slurry until the beam mold is filled, so that the concrete wraps the fiber-reinforced concrete frozen reinforcement units; After pouring, use an inserted vibrator to continuously vibrate until the concrete is uniform. After standard curing for 24 hours, demoulding takes place. During this period, the frozen reinforcement units naturally melt into slurry and undergo hydration reaction to form strength. After demoulding, the concrete components were subjected to standard curing for 28 days, and experiments were carried out to test the mechanical properties of the components.
[0028] Compared with Example 1, in the treatment process of this solution, the fiber reinforced concrete slurry is slowly frozen in a freezer at -40°C for 24 hours before initial setting, and the rest is consistent with Example 1.
[0029] Compared with Example 1, in the treatment process of this scheme, the fiber reinforced concrete slurry is quickly frozen with liquid nitrogen before initial setting, the freezing temperature is set at -100°C, and the freezing time is 180 minutes, so that the center temperature of the fiber reinforced concrete freezing enhancement unit reaches -100°C. The rest is consistent with Example 1.
[0030] Compared with Example 1, in the treatment process of this scheme, the fiber reinforced concrete slurry is placed in a standard curing room at 20±2°C and a relative humidity standard of 95% for curing for 7 days to obtain a non-frozen reinforced unit, and the rest is consistent with Example 1.
[0031] Compared with Example 1, the polyethylene fiber (PE) used in the treatment process of this solution is 2%, and the rest is consistent with Example 1.
[0032] Compared with Example 4, in the treatment process of this solution, the fiber reinforced concrete slurry is slowly frozen in a freezer at -40°C for 24 hours before initial setting, and the rest is consistent with Example 4.
[0033] Compared with Example 4, in the treatment process of this scheme, the fiber reinforced concrete slurry is quickly frozen with liquid nitrogen before initial setting, the freezing temperature is set at -100°C, and the freezing time is 180 minutes, so that the center temperature of the fiber reinforced concrete freezing enhancement unit reaches -100°C. The rest is consistent with Example 4.
[0034] Compared with Example 4, in the treatment process of this scheme, the fiber reinforced concrete slurry is placed in a standard curing room at 20±2°C and a relative humidity standard of 95% for curing for 7 days to obtain a non-frozen reinforced unit, and the rest is consistent with Example 4.
[0035] Compared with Example 4, the polyethylene fiber (PE) used in the treatment process of this solution is 2%, and the rest is consistent with Example 4.
[0036] 1. The effect of the fiber reinforced concrete reinforcement unit described in Examples 1 to 3 on the flexural strength of concrete after being built into concrete was tested, and the standard curing of ordinary concrete beams was used as a control. The results are shown in Figure 1 .
[0037] like Figure 1 As shown in the figure, after the fiber reinforced concrete slurry is quickly frozen to form a reinforcing unit and directly embedded in the bending stress concentration area of the beam, the frozen unit melts into slurry and reacts with concrete hydration to form an overall strength effect, and the overall bending resistance of the concrete beam is significantly improved. The reinforcing unit can produce a large number of microcracks in the tensile area, and the microcracks are evenly distributed in the material, thereby avoiding the occurrence of local damage and effectively sharing the load borne by the concrete. The multi-crack mechanism of the reinforcing unit not only delays the expansion of cracks, but also enables the structure to withstand greater external loads without brittle fracture, thereby improving the overall toughness of the concrete beam. The high toughness of the reinforcing unit enables the stress in the tensile area to be evenly distributed, avoiding local damage caused by stress concentration in ordinary concrete beams. In addition, the fiber can achieve fiber bridging when cracks occur, preventing the cracks from further expanding. The bridging effect significantly improves the tensile strength and toughness of the material. In addition, because of the addition of mineral admixtures and polymers, the density of the cement paste and the bonding force between the cement paste and the fiber are improved, and the mechanical properties and crack control ability of the material are enhanced. This will further improve the flexural strength of concrete, reduce plastic damage, and the strength will further increase with the curing time.
[0038] 2. The effect of the fiber reinforced concrete reinforcement unit described in Examples 4 to 6 on the shear bearing capacity of the concrete after being embedded in the concrete was tested, and the standard curing of ordinary concrete beams was used as a control. The results are shown in Figure 2 .
[0039] like Figure 2 As shown in the figure, after the fiber-reinforced concrete slurry is quickly frozen by liquid nitrogen to form a reinforcement unit, which is directly buried in the shear stress concentration area of the beam, the frozen unit melts into slurry and reacts with concrete hydration to form an overall strength effect, and the shear bearing capacity of the concrete beam is significantly improved. Under the action of shear force, ordinary concrete beams are prone to form oblique cracks in the shear zone of the beam, leading to shear failure. The cracks are usually single main cracks that extend obliquely along the shear zone of the beam. The fiber-reinforced unit, through its unique microcrack formation mechanism, produces multiple uniformly distributed microcracks in the shear zone. Microcracks can effectively disperse the shear force to avoid the expansion of local cracks, so that the beam exhibits better crack control ability when sheared. The fibers connect the materials on both sides of the crack through bridging action, which can effectively prevent the crack from continuing to expand. The crack bridging effect effectively improves the shear strength and ductility of the beam. The beam can withstand greater shear force when sheared, avoiding shear failure caused by crack expansion.
[0040] 3. The flexural strength of the concrete specimens in the technical solutions described in Example 1 and Comparative Examples 1 to 4 was tested, and the shear bearing capacity of the concrete specimens in the technical solutions described in Example 4 and Comparative Examples 5 to 8 was tested, and the standard curing of ordinary concrete beams was used as a control. The results are as follows: Figure 3 , 4 shown.
[0041] like Figure 3 , 4 As shown, compared with the technical solutions described in Comparative Examples 1 to 8, the technical solutions described in Examples 1 and 4 of the present application can make the concrete specimens have better bending / shear bearing capacity and toughness. The reason is that: Compared with the technical solution of the present application, in Comparative Examples 1 and 5, due to the slow freezing of the fiber-reinforced concrete slurry into blocks, the temperature of the slurry drops slowly during slow freezing, allowing the water to have sufficient time to migrate and aggregate to form larger ice crystals. Large ice crystals cause greater damage to the internal structure of the fiber-reinforced concrete matrix, generating large microcracks and cracks. During the slow freezing process, the fiber-reinforced concrete has incomplete hydration reaction, insufficient and unevenly distributed hydration products, and amorphous or loose hydration products of the cement particles formed by thawing, resulting in insufficient toughness of the fiber-reinforced concrete.
[0042] Compared with the technical solution of the present application, in Comparative Examples 2 and 6, the freezing temperature of fiber-reinforced concrete is set at -100°C, and the freezing time is 180 minutes to form a frozen block. When the freezing temperature is reduced to -100°C, the water in the cement-based material slurry is quickly frozen to generate a large number of ice crystals. The formation of ice crystals is dominated by ice nucleation and growth mechanisms, and ice crystals grow faster and larger at extremely low temperatures. The formation of ice crystals will occupy a certain space in the slurry, and these areas will form gaps after thawing, reducing the density and strength of the material. The freezing time is extended to 180 minutes, and long-term freezing causes microcracks on the fiber surface due to ice crystal extrusion, reducing the interfacial bonding between the fiber and the matrix. The irregular microstructure formed by cement hydration products at too low a temperature will further weaken the interfacial bonding performance. If the freezing temperature is too low and the freezing time is too long, the frozen block is prone to local thawing speed during the thawing process, resulting in too fast hydration reaction, and other parts may not be fully reacted due to too slow thawing and structural damage caused by ice crystals, resulting in uneven performance. The CSH gel formed at extremely low temperature presents an irregular morphology and lacks coherence, making it difficult to provide good strength and toughness.
[0043] Compared with the technical solution of the present application, in Examples 3 and 7, the fiber-reinforced concrete built-in concrete method with standard curing for 7 days is adopted. The surface of the fiber-reinforced concrete that has been cured for 7 days has undergone hydration reaction to generate a certain amount of hydration product CSH, while the newly poured C30 concrete is still in the rapid hydration stage. The internal stress concentration at the interface is caused by the uneven hydration reaction. This stress concentration easily leads to the formation and expansion of micro cracks on the interface. Secondly, the surface active components of the fiber-reinforced concrete are reduced, and it is difficult to form new chemical bonding products between the two concretes poured at different times, and the chemical stability of the interface is insufficient. As a result, the physical bite and chemical stability of the interface between the fiber-reinforced concrete unit and the newly poured C30 concrete are insufficient, and there is a significant difference in hydration that affects the adhesion between the concretes. The two concretes cannot be well combined, and interface cracks are prone to occur, affecting the overall mechanical properties.
[0044] Compared with the technical solution of the present application, polyethylene fibers (PE) are used to prepare fiber-reinforced concrete slurry in Comparative Examples 4 and 8. In the extremely low temperature environment of liquid nitrogen, the movement of molecular chains in polyethylene fibers is almost completely frozen, the flexibility of the material is significantly reduced, and it exhibits a more brittle behavior. This further triggers the expansion of microcracks or defects inside the fiber, thereby reducing the tensile strength and fracture strength. In addition, liquid nitrogen freezing quickly changes the crystallinity of PE fibers, causing the amorphous regions to become more brittle, thereby affecting the ductility and energy absorption capacity of the fibers. Because the temperature difference is too large, internal residual stress is introduced, which also affects the fatigue resistance and long-term load capacity of PE fibers, resulting in insufficient toughness of fiber-reinforced concrete, which affects the overall mechanical properties of concrete.
[0045] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for improving the performance of concrete components by using a freezing enhancement unit, characterized in that: The following steps are involved: (1) Using rapid freezing technology to prepare cryoenhancement units; (2) The stress concentration area of the concrete member is wrapped with at least one frozen reinforcement unit in a frozen state by pouring, and the thawed frozen reinforcement unit is combined with the concrete member through a hydration reaction by curing.
2. The method according to claim 1, characterized in that The preparation process of the cryoenhancement unit is as follows: Within 60 minutes, the reinforcement unit is frozen and formed, and its core temperature is reduced to -40~-10℃.
3. The method according to claim 1 or 2, characterized in that: The enhancement unit is Engineering fiber reinforced cementitious composite Material .
4. The method according to claim 1 or 2, characterized in that: Rapid freezing technology uses liquid nitrogen freezing, dry ice freezing or quick freezer freezing.
5. The method according to claim 1, characterized in that The freezing enhancement units are fitted to each other or have gaps therebetween.
6. The method according to claim 1, characterized in that The specific process of curing in step (2) is as follows: after pouring is completed, normal curing is performed to allow the frozen reinforcement unit to melt into slurry and combine with the hydration of the concrete component.
7. The method according to claim 1, characterized in that During pouring in step (2), the concrete properties of the frozen enhancement unit used are higher than the material properties of the concrete to be enhanced.
8. A concrete component, characterized in that: The method is prepared by any one of claims 1 to 7.
Citation Information
Patent Citations
Fiber reinforced concrete raw material, fiber reinforced concrete and preparation method and application thereof
CN110330273A
Novel method for reinforcing and toughening concrete and concrete
CN113716901A
Preparation method and application of cement-based hydrogel composite electrolyte material
CN114920510A
Preparation method of anti-scouring layer based on frozen blocks
CN118026596A
Mass concrete temperature control and shrinkage compensation method
CN118026729A